Public sector unions, corporation, and macroeconomic performance - Garrett, Geoffrey; Way, Christopher (1999)
What accounts for the apparent breakdown of the positive relationship between powerful trade union organizations and macroeconomic performance? Is corporatism a relic of a different age, a luxury of the long postwar boom? Although the authors answer the latter question in the negative, they do contend that existing arguments about the macroeconomic consequences of corporatism should be significantly modified to take into account the impact of the growth of public sector unions on the relationship between institutional structure of labor movements and economic outcomes. The deteriorating performance commonly attributed to corporatism in the 1980s was limited to countries in which unions in the public sector and other sectors not exposed to international competition increasingly dominated national labor movements. Encompassing trade union movements can still generate wage restraint, but only where the union movement is dominated by unions in the exposed sector that are subject to the constraints posed by international market competition. - Reproduced
Keywords: Trade unions